2017
DOI: 10.1016/j.foodchem.2016.07.108
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of proline decreases immunoreactivity and alters structure of barley prolamin

Abstract: Elimination of celiac-toxic prolamin peptides and proteins is essential for Triticeae products to be gluten-free. Instead of enzymatic hydrolysis, in this study we investigated metal-catalyzed oxidation of two model peptides, QQPFP, and PQPQLPY, together with a hordein isolate from barley (Hordeum vulgare L.). We established a multiple reaction monitoring (MRM) LC-MS method to detect and quantify proline oxidation fragments. In addition to fragmentation, aggregation and side chain modifications were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…With the increasing concentration of AAPH, the content of the α‐helix decreased at 0–0.2 mmol/L AAPH and then increased at 0.2–10 mmol/L AAPH, the change in the β‐sheet content was exactly the opposite to that of the α‐helix content, while the β‐turn content and random coil content were increased significantly. Normally, the oxidation of AAPH causes the ordered α‐helix and β‐sheet structure in EYHDL to transform into a disordered random coil and β‐turn structure, and the increased α‐helix content in EYHDL under high‐oxidant conditions was different from that reported in previous related studies (Huang, Sontag‐Strohm, Stoddard, & Kato, ; Wang, He, Gan, & Li, ). Moderate oxidation can induce partial unfolding of the proteins, thereby exposing certain sites that are normally hidden within proteins (Estévez, ) and leading to a reduction in the intramolecular hydrogen bonds.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…With the increasing concentration of AAPH, the content of the α‐helix decreased at 0–0.2 mmol/L AAPH and then increased at 0.2–10 mmol/L AAPH, the change in the β‐sheet content was exactly the opposite to that of the α‐helix content, while the β‐turn content and random coil content were increased significantly. Normally, the oxidation of AAPH causes the ordered α‐helix and β‐sheet structure in EYHDL to transform into a disordered random coil and β‐turn structure, and the increased α‐helix content in EYHDL under high‐oxidant conditions was different from that reported in previous related studies (Huang, Sontag‐Strohm, Stoddard, & Kato, ; Wang, He, Gan, & Li, ). Moderate oxidation can induce partial unfolding of the proteins, thereby exposing certain sites that are normally hidden within proteins (Estévez, ) and leading to a reduction in the intramolecular hydrogen bonds.…”
Section: Resultscontrasting
confidence: 58%
“…Normally, the oxidation of AAPH causes the ordered α-helix and β-sheet structure in EYHDL to transform into a disordered random coil and β-turn structure, and the increased α-helix content in EYHDL under high-oxidant conditions was different from that reported in previous related studies (Huang, Sontag-Strohm, Stoddard, & Kato, 2017;Wang, He, Gan, & Li, 2018). Moderate oxidation can induce partial unfolding of the proteins, thereby exposing certain sites that are normally hidden within proteins (Estévez, 2011) and leading to a reduction in the intramolecular hydrogen bonds.…”
Section: Changes In the Secondary/tertiary Structure Of Oxidized Eyhdlmentioning
confidence: 68%
“…For biochemical processing, usage of food-grade microbial transglutaminase (mTG) with lysine ethyl ester is able to modify gliadin peptides, which inhibits the ability of gluten to trigger the specific human immune response in vitro [4]. Huang et al (2017) found a metal-catalyzed oxidation system can cause the modification and elimination of hordein, leading to the decrease of immunoreactivity of hordein [5].…”
Section: Introductionmentioning
confidence: 99%
“…In model systems, peptides QQPFP and PQPQLPY derived from barley hordein were oxidized at different positions in the presence of hydroxyl radicals and the authors concluded that this might explain the reduce immunoreactivity of the oxidized hordein because QQPFP and PQPQLPY are core parts of T‐cell stimulating peptides (Huang, Sontag‐Strohm, Stoddard, & Kato, ). Di‐tyrosine was formed through oxidation of peptide PQPQLPY with hydroxyl radicals but not with ascorbic acid and in addition, the degradation of proline was more pronounced in QQPFP than in PQPQLPY although, the later has more proline residues (Huang et al, ). This emphasizes the importance of the structure (i.e., sequence) on the reactivity of food peptides with HO• radicals as in this case proline at the C‐terminal is more readily attacked by this reactive species.…”
Section: Reaction Of Peptide With Hydroxyl Radicalsmentioning
confidence: 99%